2012
DOI: 10.4314/ejesm.v5i4.s13
|View full text |Cite
|
Sign up to set email alerts
|

Soil Loss Estimation through USLE and MMF Methods in the Lateritic Tracts of Eastern Plateau Fringe of Rajmahal Traps, India

Abstract: Laterites of Birbhum district are indentified as the 'low-level laterites' of 'Rarh Plain' of West Bengal and these are very much prone to severe soil erosion (mainly surface and sub-surface water erosion) in the monsoon season (June -September). Laterites and lateritic soils (locally named 'Kankara') of Caniozoic upland (adjoining areas of Rampurhat I block, Birbhum and Shikaripara block, Dumka-the study area), are the direct result of monsoonal wet-dry type of morpho-climatic processes and further laterisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The water phase determines the energy of rain offered to detach soil particles from the soil mass and carried with the surface runoff. The erosion phase regulates the rate of soil particle detachment by rain and runoff and is determined in conjunction with the transport capability of runoff [17,[28][29][30]. This model is highly sensitive to the annual rain and soil parameters, once erosion is transport-limited [17].…”
Section: Introductionmentioning
confidence: 99%
“…The water phase determines the energy of rain offered to detach soil particles from the soil mass and carried with the surface runoff. The erosion phase regulates the rate of soil particle detachment by rain and runoff and is determined in conjunction with the transport capability of runoff [17,[28][29][30]. This model is highly sensitive to the annual rain and soil parameters, once erosion is transport-limited [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in the same areas, has been done by Pandey et al (2007), in which they have identified the critical erosion prone areas using USLE model through GIS and remote sensing techniques and found that the differences between the observed and the estimated soil loss. A study by Ghosh and Guchhait (2012), have estimated soil loss using USLE and Morgan, Morgan and Finney (MMF) methods in the lateritic tracts of Jharkhand and found that the estimated soil loss is greater in the MMF method than in the USLE method in most of the soil types. Soil loss estimation has also been done in the southern regions of India by Prasannakumar et al (2012).…”
Section: Introductionmentioning
confidence: 99%